Nurse prescribing in end-of-life care in the community: meeting patients' needs. (11th November 2021) - Latter, Susan
Abstract : This article outlines the important role of medicines in managing community-based palliative care in the last year of life, together with the central role of nurses prescribing in this context. The article discusses the key needs of patients and carers managing palliative care medicines in the home setting, which include a requirement for streamlined, rapid access to medicines, as well as information about and support for daily self-management of medicines. The article draws on recent research in the field of palliative care medicines management and highlights the implications for nurse prescribers.